2011
DOI: 10.1007/s10528-011-9424-x
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Contribution of Northern Chinese to the Paternal Genetic Structure of Chaoshanese in South China

Abstract: We investigated the Y chromosome of various Chinese populations to determine the patrilineal origin of the Chaoshanese population. Admixture analysis of six specific Y short tandem repeat (STR) loci in 6,292 individual samples taken from 51 populations, including Chaoshanese and Minnanese of our earlier studies, showed that over 85% of the Chaoshanese Y chromosomes were derived from the Central China Han (M (RH): 0.8614; M (BE): 1.1868 ± 0.2054), and a very small portion were from the southern aborigines. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
2
2
0
Order By: Relevance
“…The NPC and NC populations are located closely within the southern Han population cluster. This pattern was well consistent with what we had previously reported on the genetic origin of the Chaoshanese by using both HLA [39] and short tandem repeat [40], [41] data. It is noticeable that our NPC and NC samples gathered with the two reported Chaoshan populations (CS1 [42] and CS2 [43]) within the southern Han population cluster (Figure 1), but these populations do not appear to be as closely as they were supposed to be.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The NPC and NC populations are located closely within the southern Han population cluster. This pattern was well consistent with what we had previously reported on the genetic origin of the Chaoshanese by using both HLA [39] and short tandem repeat [40], [41] data. It is noticeable that our NPC and NC samples gathered with the two reported Chaoshan populations (CS1 [42] and CS2 [43]) within the southern Han population cluster (Figure 1), but these populations do not appear to be as closely as they were supposed to be.…”
Section: Resultssupporting
confidence: 93%
“…To demonstrate that the NPC patients and control subjects analyzed in this study were generally homogenous and had no remarkable difference compared with those previously reported Chaoshan populations [39][41], we performed a PC analysis, based on mtDNA haplogroup frequencies, for the NPC and NC groups, together with the reported Chaoshanese [42], [43] and other Han Chinese populations (Table S1). As shown in Figure 1, the cumulative contribution of PC1 and PC2 accounts for 83.9% of the total variation, and the northern and southern Han populations each fall into their respective clusters, which are distinctly separated by PC2, with the northern Hans clustering together in the upper part of the plot and the southern Hans in the lower part.…”
Section: Resultsmentioning
confidence: 90%
“…Interestingly, the haplotype that matched with our data happened to be within a Singapore Han population. This appeared to be consistent with what we observed in our previous phylogenetic study on Y-chromosomal haplotypes, in which Minnan people clustered closely with Singapore Chinese regardless of the geographic distance between the two populations [16] . Furthermore, the result seemed to conform also to a well accepted concept that population structure is more pronounced in Y-chromosomal genetic databases [13,17] .…”
Section: Discussionsupporting
confidence: 92%
“…Ultimately, 2420 participants (904 from North of China, 1516 from South) were included in the analysis (figure 1), with the detailed number of participants enrolled from each province/municipality listed in online supplementary table 1. For all statistical analysis, we divided the participants into three groups according to their glucose metabolism status: (1) normal glucose tolerance (NGT): [8][9][10] and the genetic structure of the Han Chinese using genome-wide association study (GWAS) data showed that the genetic background of Henan Han Chinese is closest to people from Jiangsu province. 11 As a result, the population metabolic feature of Henan Han Chinese, such as overweight and obesity, is similar to Jiangsu province and significantly different from the typical North provinces.…”
Section: Methods Study Participantsmentioning
confidence: 99%